Zircon U–Pb geochronology and geochemistry of granitic rocks in central Mongolia - Dolzodmaa, Boldbaatar; Osanai, Yasuhito; Nakano, Nobuhiko; Adachi, Tatsuro (Mongolian Geoscientist, 2020)
The Central Asian Orogenic Belt had been formed by amalgamation of voluminous subduction–accretionary complexes during the Late Neoproterozoic to the Mesozoic period. Mongolia is situated in the center of this belt. This study presents new zircon U–Pb geochronological, whole-rock major and trace element data for granitoids within central Mongolia and discusses the tectonic setting and evolution of these granitic magmas during their formation and emplacement. The zircon U–Pb ages indicate that the magmatism can be divided into three stages: the 564–532 Ma Baidrag granitoids, the 269–248 and 238–237 Ma Khangai granitoids. The 564–532 Ma Baidrag granitoids are adakitic, have an I-type affinity, and were emplaced into metamorphic rocks. In comparison, the 269–248 Ma granitoids have high-K, calc-alkaline, granodioritic compositions and are I-type granites, whereas the associated the 238–237 Ma granites have an A-type affinity. The 564–532 Ma Baidrag and 269–248 Ma Khangai granitoids also both have volcanic arc-type affinities, whereas the 238–237 Ma granites formed in a post-collisional tectonic setting. These geochronological and geochemical results suggest that arc magmatism occurred at the 564–532 Ma which might be the oldest magmatic activity in central Mongolia. Between the Baidrag and the Khangai, there might be paleo-ocean and the oceanic plate subducted beneath the Khangai and produced voluminous granite bodies during the 269–248 Ma. After the closure of the paleo-ocean, the post collisional granitoids were formed at the 238–237 Ma based on the result of later granitoids in the Khangai area.